2016
DOI: 10.1002/dc.23642
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration in the diagnosis and classification of hepatoblastoma

Abstract: FNA allows to accurately diagnose HBL and recognize its histological subtypes. On the basis of high concordance between cytological and histological diagnosis, FNA is validated as an alternative diagnostic method to CNB. Diagn. Cytopathol. 2017;45:91-100. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
2
17
1
Order By: Relevance
“…Necrosis was present in cases, regardless of their subtype. Similar cytoplasmic vacuolization was also reported by Vlajnic et al, but necrosis, apoptosis, and mitotic figures were not seen in the fetal component in comparison with the embryonal component. Certain unusual features such as the presence of mast cells, foamy macrophages, and plasmacytoid morphology for fetal cells were observed that have not been reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Necrosis was present in cases, regardless of their subtype. Similar cytoplasmic vacuolization was also reported by Vlajnic et al, but necrosis, apoptosis, and mitotic figures were not seen in the fetal component in comparison with the embryonal component. Certain unusual features such as the presence of mast cells, foamy macrophages, and plasmacytoid morphology for fetal cells were observed that have not been reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, various architectural patterns were identified in HB: trabecular and perivascular patterns were more common in fetal HB, whereas acinar and cluster formation was more common in embryonal HB, as observed in previous studies . The identification of the arrangement of tumor cells in HB aids in differentiating it from childhood HCC.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations